Sterically controlled silacycloalkyl diamide complexes of titanium(IV): Synthesis, structure, and catalytic behavior of (cycl)Si(NBut)(2)TiCl2 [(cycl)Si = silacyclobutane, silacyclopentane, silacyclopentene, and silacyclohexane] - Kim, SJ; Jung, IN; Yoo, BR; Kim, SH; Ko, JJ; Byun, DJ; Kang, SO (AMER CHEMICAL SOC, 2001)
The chemistry of titanium complexes stabilized by a series of cyclic silyldiamide ligands (cycl)Si(HNBut)(2) (2) derived from the silacycloalkyl unit -(CH2)(n)Si-, with n = 3, 4, and 5, has been studied. Thus, a variety of spiro-siladiazatitanacyclobutane complexes (cycl)Si(NBut)(2)TiCl2 (3) has been prepared by the reaction of the dilithium salt of 2 with titanium tetrachloride. The reaction of 2 with Ti(NMe2)(4) in refluxing toluene yields (cycl)Si(NBut)(2)Ti(NMe2)(2) (4), and the product 4 is converted to 3 in a moderate isolated yield by treatment with excess Me3SiCl. Dimethyl complexes of the type (cycl)Si(NBut)(2)TiMe2 (5) were prepared by the reaction of 3 with MeMgBr. Complexes 3 have been characterized by X-ray crystallography. As a result of the formation of the siladiazatitanacyclobutane ring, the titanium atoms in 3 exhibit distorted-tetrahedral configurations with the two chloride ligands. in addition, the crystallographic results establish that steric interactions between the silacycloalkyl and tert-butyl groups influence the C(Bu-t)-N-Ti angles and, hence, the steric environment at titanium. The compounds 3 were further investigated as potential catalysts for the polymerization of ethylene. While sterically less demanding silacyclobutyl and -pentyl diamide complexes (3a and 3b) exhibit low ethylene polymerization activity (4.0-5.8 kg PE mol(cat)(-1) h(-1)) in the presence of methylalumoxane, the highly puckered silacyclohexyl diamide complex 3c shows better activity (14 kg PE mol(cat)(-1) h(-1)) for ethylene polymerization when it is activated with MAO.
Keywords: ZIRCONIUM COMPLEXES; MOLECULAR-STRUCTURE; ALPHA-OLEFINS; LIVING POLYMERIZATION; METAL-COMPLEXES; LIGANDS; CRYSTAL; DERIVATIVES; GROUP-4; ELEMENTS